Energy efficient data transmission on the internet - Guo-qiang ZHANG; Sen LIN; Zhen LIU; Tao LIN; Guo-qing ZHANG; You-ping LI (Tongxin xuebao)
Approaches for reducing network energy consumption were surveyed from two aspects:realizing energy-proportional computing in data transmission,and reducing duplicated data transmission in the network.Approaches endeavor to realize energy-proportional computing include network presence proxy in edge networks,energy-efficient Ethernet and energy-aware routing techniques in core network.The asynchronous data access nature and the heavy-tailed frequency distribution for data access offer opportunities to reduce duplicated data transmission.Several existing and experimental content distribution mechanisms (e.g.,CDN,P2P,CCN and dually structured internet) and their effects in enhancing energy efficiency in data transmission,were compared and investigated.